2013
DOI: 10.1002/lt.23771
|View full text |Cite
|
Sign up to set email alerts
|

Regional perfusion by extracorporeal membrane oxygenation of abdominal organs from donors after circulatory death: A systematic review

Abstract: Organs from donors after circulatory death (DCDs) are particularly susceptible to the effects of warm ischemia injury. Regional perfusion (RP) by extracorporeal membrane oxygenation (ECMO) is increasingly being advocated as a useful remedy to the effects of ischemia/reperfusion injury, and it has been reported to enable the transplantation of organs from donors previously deemed unsuitable. The MEDLINE, Embase, and Cochrane databases were searched, and articles published between 1997 and 2013 were obtained. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 66 publications
(102 reference statements)
0
42
1
2
Order By: Relevance
“…In some small studies, 1 year patient and graft survivals after ECMO-RP of donor kidneys were better than DCD and were comparable with DBD organs. 3,13,14 However, with regard to liver transplantation, ECMO-RP was associated with high rates of primary nonfunction, graft failure, and post-transplantation complications. Thus, authors have suggested that RP for liver transplantation be approached with caution.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In some small studies, 1 year patient and graft survivals after ECMO-RP of donor kidneys were better than DCD and were comparable with DBD organs. 3,13,14 However, with regard to liver transplantation, ECMO-RP was associated with high rates of primary nonfunction, graft failure, and post-transplantation complications. Thus, authors have suggested that RP for liver transplantation be approached with caution.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, authors have suggested that RP for liver transplantation be approached with caution. 13 Additional considerations with regard to ECMO include the resource-heavy implications of using such a technology. It is unlikely that many of the smaller hospitals where organ donation often takes place have ECMO units, and the expense and expertise required in developing and providing portable ECMO units for procurements limits the excitement for this.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal regional perfusion is being done via cannulation of femoral artery and vein using cardio pulmonary bypass machine or extracorporeal membrane oxygenation machine. For the first time regional perfusion was performed by a Spanish surgeon at 1989 [42] . The perfusion is being used in two categories after one hour of WIT [32] .…”
Section: Abdominal Regional Perfusionmentioning
confidence: 99%
“…3e5 The main problem in LT is the wide disparity between supply (available donors) and demand (patients needing liver grafts). 3e5 To increase the pool of donors from the conventional beating heart, brainstem-dead donors, various effortsdsuch as using marginal donor from controlled non-heart beating donor by perfusion of cold preservation solution in the femoral artery immediately after cardiac arrest, 6 or regional extracorporeal membrane oxygenation (ECMO) perfusion of the abdominal organs after cardiac arrest, 7 or systemic ECMO support after cardiac deathdhave been performed. 8 Improvement in the surgical technique via using reduced liver graft has shortened the waiting period of pediatric recipients and eliminated death in the waiting list.…”
Section: Introductionmentioning
confidence: 99%